A Systematic Literature Review of Project-Based Learning Models in En-hancing EFL Learners’ English Writing Skills - Gilang Rizkia Aditia; Sri Astuti (Insan Akademika Publications, 2026)
The increasing emphasis on communicative competence in English as a Foreign Language (EFL) instruction highlights the need for effective pedagogical approaches to improve learners’ writing skills. Project-Based Learning (PjBL) has gained attention as an instructional model that integrates authentic tasks, collaboration, and learner autonomy in writing instruction. This study aims to systematically examine the role of Project-Based Learning in enhancing EFL learners’ English writing skills based on empirical studies published between 2023 and 2025. Employing a qualitative Systematic Literature Review (SLR), this study follows the PRISMA 2020 guidelines and applies the PICOS framework to define the scope of analysis. Literature searches were conducted using the Scopus, Web of Science, ERIC, and Google Scholar databases with predefined Boolean search strategies. The initial search yielded 91 journal articles, which were screened using established inclusion and exclusion criteria. Through the selection and data charting process, 13 peer-reviewed empirical studies were identified and systematically analyzed. The selected studies were synthesized in a matrix table of study characteristics and analyzed using thematic synthesis and descriptive analysis to identify patterns related to PjBL designs, project types, writing components, and reported challenges. The findings indicated that Project-Based Learning consistently improves EFL learners’ writing performance, particularly in content development, text organization, vocabulary use, and learner engagement. However, improvements in micro-linguistic aspects such as grammatical accuracy, cohesion, and writing mechanics are less consistently reported. This review highlighted methodological limitations in existing studies and offers implications for pedagogy and future research, particularly regarding longitudinal designs, cross-genre writing development, and digital integration.